Mental Health and Conflict - Baingana, Florence (World Bank, Washington, DC, 2012)
Addressing mental health is gradually being recognized as an important development issue, especially in the case of conflict-affected countries. Although mental health issues have received increased attention in post-conflict settings, there has been a tendency to implicitly assume that the impact of trauma caused by mass violence (i) may be transitory and non-disabling, and (ii) that interventions in the emergency phase are sufficient. However, a small but growing body of research on factors affecting mental health and effective treatment in postconflict settings casts doubts on both assumptions. Current research suggests that major depression and Post-Traumatic Stress Disorder (PTSD) are prevalent and chronic among refugee and displaced populations. Research also shows that the impact of trauma is long term. Child survivors of Nazi holocaust and Japanese concentration camps were found to experience PTSD symptoms as late as 40-50 years following their traumatic experience. Some researchers postulate that these 'invisible wounds' can leave a society vulnerable to a recurrence of violence. Studies on Nazi Holocaust and Cambodian Pol Pot survivors show that their children and their children's children are also affected by the psychosocial impact of conflict.